Pathology of the Economic Council in Pahlavi 2nd's period Concerning the Economic Development, A Historical Review - Rahim Abedini; Abolhasan Fayyaz Anosh; Morteza Dehqannejad (تاریخ اسلام)
One of the institutions established in time of Pahlavi II  to achieve the economic development was the Economic Council held on Mondays in front of the Pahlavi King with the presence of the government's economic team. The current article focuses on the "Issue of Iran's Economic Development" and examines the minutes of the Economic Council. This study, based on Rosen Stein Roden's "balanced economic growth theory", has analyzed the issues raised in the meeting minutes in order to find the answer to this question on what effect the Economic Council had on Iran's economic development process. The memories of agents present in the meetings for two decades have also been used as another source. Moreover, the report of evaluations of various departments of the Program and Budget Organization regarding construction plans has been considered and used to confirm the analysis. The findings of the research clarify that due to the lack of coherence and the lack of a general view in the economic decisions, heterogeneity in dealing with different economic sectors and the how of making decisions in this council, its results could not lead to a balanced and sustainable development of Iran.